ANALISA INTEGRASI APLIKASI AKUNTANSI BERBASIS SAAS. STUDI KASUS PADA XYZ.COM - Danny Yudin Djahidin (ULTIMA InfoSys, 2020)
SaaS application users get strategic benefits, among them the speed of implementation, reliability, and flexibility also optimization of infrastructure capacity. The company does integration with the aim to increase productivity, data accuracy, speed and flexibility [1]. This also drives XYZ.com, an online store in Jakarta, to integrate its web commerce application with SaaS accounting application. System integration design is carried out by analysis and observation of current business processes using the business objectives model. It is concluded that with system integration, XYZ.com wants to achieve 3 business objectives, i.e. (1) increasing the number of orders recorded in the accounting application, (2) improving stock accuracy, and (3) reducing the number of order cancellations due to unavailability of goods. System integration is designed to enable information retrieval such as products, contacts, transactions, and journals from accounting application through available API. Further research needs to be carried to realize the list of requirements that have been described in the feature tree to the stage of software development and implementation so that the objectives set by the business can be measured and improved.